Efektivitas Antidiabetes Fraksi Air Daun Karamunting (Rhodomyrtus Tomentosa (Ait.) Hassk.) terhadap Kadar Glukosa Darah dan Sekresi Insulin pada Tikus Model Diabetes - Geri Febriyanto; Mgs. Irsan Saleh; Theodorus Theodorus (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2021)
This study aims to determine the effectiveness of the water fraction of caramunting leaves (Rhodomyrtus tomentosa (Ait.) Hassk). Against a decrease in blood glucose levels 2 hours post prandial and an increase in insulin levels of male white rats induced by streptozotocin. This research is an in vivo laboratory experimental research. The subjects of this study were 30 male white rats divided into 5 groups, namely positive control using glibenclamide, negative control using Na CMC, treatment group using caramunting leaf water fraction 70mg/ KgBB, 140mg/ KgBB, and 280mg / KgBB. The results showed that the caramunting leaf water fraction group was 70mg/ KgBB. 140mg/ KgBB, and 280m / KgBB effectively reduce blood glucose levels 2 hours post prandial and increase insulin levels. Based on the results obtained, it can be concluded that the water fraction of caramunting leaves (Rhodomyrtus tomentosa (Ait.) Hassk). Effectively reducing blood glucose levels 2 hours post prandial and increasing insulin levels with a dose of 280mg / KgBB is the most effective dose.